2019
DOI: 10.24200/jonus.vol4iss1pp49-68
|View full text |Cite
|
Sign up to set email alerts
|

Moving Onward: Transnationalism and Factors Influencing Rohingyas’ Migration From Bangladesh to Malaysia

Abstract: Continuous human rights persecutions have forced nearly one million Rohingyas to flee from Myanmar and seek refuge in Bangladesh. While their forced migration to the first asylum country of Bangladesh is inevitable, some have been compelled to move onward to other transit countries. Existing studies indicate various factors influencing cross-border activities among different segments of immigrants. They also suggest that the degree of transnationalism affects different kind of people on the move, subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The best strategy would be to use traditional and widely used methods of information dissemination. Rohingya NGOs can assist UNHCR in providing beneficiaries with information-based geographic displacement information capable of completing spatial descriptions as needed in promoting international human rights by developing and disseminating computerized refugee registration methods [10] . This can be accomplished by giving them the impression that refugees and refugee claimants can be well-handled within the system and that no free person should be left outside the system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The best strategy would be to use traditional and widely used methods of information dissemination. Rohingya NGOs can assist UNHCR in providing beneficiaries with information-based geographic displacement information capable of completing spatial descriptions as needed in promoting international human rights by developing and disseminating computerized refugee registration methods [10] . This can be accomplished by giving them the impression that refugees and refugee claimants can be well-handled within the system and that no free person should be left outside the system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interviews also revealed that some Rohingyas and Hazaras ran teashops and small restaurants. While some accessed microfinance managed by NGOs, most borrowed money through their social networks of families and friends (Wahab, 2017;Wahab and Khairi 2019). It appears that in addition to financial capabilityincluding, at least, initial capital and business and Malay language skillsa migrant's relationship with the local Malay community and businesspersons was key to running an enterprise.…”
Section: Beyond Bare Life: Refugees' Life Projectsmentioning
confidence: 99%
“…In Southeast Asia, Malaysia is home to the largest number of refugees and asylum-seekers, the majority of whom are Muslim (Hussain 2017;UNHCR 2022). Muslim refugees from the Middle East and South Asia prefer Malaysia, due to its image as a progressive Islamic country (Wahab and Khairi 2019).…”
Section: Constructing and Supporting Refugees' Bare Lifementioning
confidence: 99%
“…After leaving Myanmar or the camps of Bangladesh, Rohingya refugees often seek to reach Malaysia because it has generally shown its generosity to Rohingya refugees arriving by boat or through land [ 3 ]. Moreover, most Rohingya refugees seek to travel to Malaysia because the country has similar religious beliefs and because of the relative ease of securing jobs as refugees [ 4 ]. There is also a lesser likelihood of alienation or isolation as an informally settled Rohingya community has been distributed throughout Malaysia for two to three generations [ 5 ].…”
Section: Introductionmentioning
confidence: 99%